The effect of mutual coupling on the noise performance of large antenna arrays - Van der Merwe, Jacki (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.